Atmosfera controlada e temperatura de armazenamento na qualidade fisiológica e química de sementes e grãos de soja - Ludwig, Vagner (2019)
In Brazil, there is a deficit of soybean and grain storage capacity to maintain seed physiological quality and chemical grain quality. Reduction of partial oxygen pressure (O2) and increase of carbon dioxide partial pressure (CO2) could maintain seed physiological potential and soybean grain quality during storage, due to reduced respiration and lipid degradation. The objective of this work was to evaluate the effect of different concentrations of oxygen (O2) and carbon dioxide in controlled atmosphere combined with different temperatures on the maintenance of the physiological potential of seeds and chemical characteristics of soybean grains. In the year 2017, the cultivars Brasmax Desafio RR and TEC IRGA 6070 RR were used. The seeds were kept for seven months under the following conditions [1] environment; [2] 1.0 kPa O2 + 0.04 CO2; [3] 2.0 kPa O2 + 0.04 CO2; [4] 2.0 kPa O2 + 30 CO2; [5] 2.0 kPa O2 + 80 CO2. In 2018 the cultivar NA 5909 RR and Fepagro 37 RR were used. The seeds were kept for 7 months under the following conditions [1] environment; [2] 1.0 kPa O2 + 0.04 CO2; [3] 1.0 kPa O2 + 15 CO2; [4] 1.0 kPa O2 + 30 CO2; [5] 2.0 kPa O2 + 0.04 CO2. In both years the cultivars were stored at temperatures of 20, 25 and 30 ºC. For seed physiological quality evaluation the following parameters were evaluated: germination standard test, sand emergence, field emergence, shoot and root length and dry mass and electrical conductivity. For the chemical quality evaluation, peroxide index, acidity index and volatile compounds of the ground grains were evaluated. The condition of 1.0 kPa O2 maintained higher percentage of germination after seven months of storage, however it is not recommended to use a temperature above 25 ° C during storage. Higher partial pressure of CO2 did not present positive effects on the physiological potential of the seeds of cultivars TEC IRGA 6070 RR, Brasmax Desafio RR and Fepagro 37 RR. At 20 ºC all cultivars reached the minimum germination standard, according to the legislation. The temperature of 25ºC is not recommended for Brasmax Desafio RR storage, regardless of the controlled atmosphere condition. The cultivar NA 5909 RR reached the germination pattern at all temperatures used in the study and the ambient air condition (without controlled atmosphere) is not recommended to store this cultivar at 25 e 30 ºC . The peroxide and acidity indexes were higher in grains stored at ambient air condition, evidencing more deterioration of the oil quality. In addition, the compound trans-2-hexenal showed high correlation with the acid and peroxide indexes, and may be an important marker of lipid oxidation of soybean grains.